What Kaaps brings to the table : a sociolinguistic analysis of the intersection between language, food and identity in Vannie Kaap memes - Roman, Samantha (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.